Compilation of psychological security training package for teenagers with mental insecurity - Fatahi Dolatabadi, Alireza; Atashpour, Seyed Hamid; Golparvar, Mohsen (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Adolescence research is a life stage of an individual’s life cycle in which a teenager experiences all-round physical-cognitive-moral and behavioral changes and transformations. This life stage is when changes in the roles and responsibilities of a person occur based on society’s expectations of him as an adult. This study was conducted with the aim of developing a special psychological safety training package for adolescents suffering from psychological insecurity. Methods: This research was qualitative and content analysis based on the method of Heish and Shannon (2005). The research environment was all the texts related to psychological security and psychological insecurity of adolescents, 17 texts were selected and analyzed based on the inclusion and exclusion criteria. Results: The results of content analysis showed five main concepts, which were: 1) security based on self-perception and acceptance, 2) spiritual security, 3) perceived moral and legal security, 4) security based on social capacities and 5) communication and family security. Conclusion: School counselors and adolescent counselors in behavioral correction centers can use this method to improve the mental health of adolescents.